Ultra-wideband SOA fibre laser / Nor Ahya Hassan - Hassan, Nor Ahya (2015)

(untitled)
A comprehensive study has been conducted on an ultra-wideband semiconductor optical amplifier (SOA) for the generation of ultra-wideband fibre lasers of various attributes throughout this dissertation. The fundamental characteristics of the ultrawideband SOA such as the gain and noise figure (NF) are successfully investigated by utilizing the conventional method of measurement and described in the earlier part of the thesis. A result of high gain with small NF drawbacks and coverage of three communication bandwidth regions of more than 120 nm, of short (S-) band, conventional (C-) band and long (L-) band is achieved. The ultra-wide band coverage of the telecommunication bandwidth has made the ultra-wideband SOA a promising candidate to reduce dependency on the costly rare earth doped fibres that dominates the communication industry nowadays. The characterization technique of double-pass configuration of the ultra-wideband SOA also has attained attractive results on gain and NF values. This characterization is crucial in later experiments regarding ultra-wideband SOA fibre laser generation. The ultra-wideband fibre lasers are realized by utilizing three experimental configurations; by using arrayed-waveguide grating (AWG), by using three wavelength selective filters of fibre Bragg gratings (FBGs), and by applying nonlinear effect in the optical fibre of stimulated Brillouin scattering (SBS) effect. The method using AWG produces a 16-channel system of an ultra-wideband multi-wavelength SOA fibre laser. The occurrence of a single wavelength signal of every S-, C- and L-band simultaneously for every selected channel has been the main highlight of this laser configuration. Other than that, this configuration also has the favourable factor of wavelength tunability within the aforementioned bandwidth range. iii The method that deploys three FBGs, representing S-, C- and L-band as the wavelength selective filters, produces three simultaneous signal wavelengths with high average signal-to-noise ratio (SNR) at the maximum drive current of ultra-wideband SOA. The proposed system would find many applications where a wide-band and stable laser source is crucial, such as in communications and sensing. The third method deployed is by applying nonlinear effects into a high nonlinear fibre of dispersion compensating fibre (DCF). This experimental configuration yields three sets of multi-wavelength laser comb of S-, C- and L-band simultaneously, with about 0.08 nm wavelength spacing (equal to 10 GHz in frequency frame) in each wavelength comb. This system has the advantage of the ability to supply many wavelength signals at one time, which is highly demanded in the dense wavelength division multiplexing (DWDM) system application. All the three ultra-wideband SOA fibre laser systems are tested for stability tests of 70 minutes duration running time. This is to prepare for a stable fibre laser system into the network applications.